Barriers and facilitators of the implementation of the application of pelvic floor muscle training in patients with prostate cancer: a scoping review - Wang, Lijuan; Li, Yaqin; Qi, Ziyi; Wang, Wei (Frontiers in Public Health, 2023)
Background:Patients with prostate cancer (PCa) benefit significantly from pelvic floor exercises, but recent results indicate that these exercises have not been fully promoted in clinical settings. This scoping review aimed to identify the facilitators and barriers of pelvic floor muscle training (PFMT) in PCa survivors. Methods:A scoping review was conducted in November 2022. Relevant studies were identified via CINAHL, Embase, PubMed, PsycINFO, and Web of Science from database inception to November 20, 2022. Data were analyzed and extracted by two formally trained researchers. Results：A total of 53 studies were included, most of which were randomized controlled trials. TheTailored Implementation for Chronic Diseases model framework(TICD)was used to identify the contents of seven barriers and promotion areas, as well as a series of sub-domains. The most common barriers to implementing pelvic floor muscle training( PFMT) included: the lack of a common scheme in guidelines and the measurement of common standardized outcomes, inadequate self-monitoring or feedback from healthcare professionals to improve PFMT compliance, poor patient compliance, and a lack of implementation equipment and financial support. Good treatment effects and easy operation were the facilitators of PFMT. Conclusion:The implementation of PFMT faces a number of challenges and opportunities that should be understood thoroughly before implementation. In terms of guidelines and clinical practice, more work is needed , and the possibility of PFMT implementation in various hospitals and community health centers or clinics should be considered.